Systemic Risk in Vietnam Stock Market - Vu, Thi Thuy Van; Tran, Dang Kham (Asian Economic and Financial Review, 2019)
Systemic risk is one of the issues currently being paid attention to in ensuring the stability and sustainability of the global financial system in general and the securities market of countries in particular. The paper studied the systemic risk of enterprises listed on Ho Chi Minh City Stock Exchange in the period from the first quarter of 2010 to the second quarter of 2017. The authors have applied the VaR and CoVaR method to compare the loss level of businesses to the systemic risk of the whole market upon an unstable event. The study also found a disadvantage of using VaR in measuring systemic risk in that it was still "individual" and "single" and didn’t consider the spread among various entities in the market. In addition, the sensitivity of listed companies varied under normal and volatile conditions. The results showed that CoVaR is a more suitable measure in considering the contribution level of companies to the systemic risk of the whole market. Calculated results were proposed as an indicator for investors and market managers in order to limit systemic risks in the future.